(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This article is experiences and concepts on improving the collaborative competence of family and women’s system. Decisive importance in ensuring the effectiveness of the reforms implemented in the field of professionalism of the employees of the Family and Women’s System. Also social and pedagogical improvement of collaboration competences of workers of a system of family and women`s.